Corrosion-resistant ceramic glaze and method for preparing ceramic product by using same
By using corrosion-resistant ceramic glaze composed of inner layer materials composed of kaolin, quartz, etc. and outer layer materials such as epoxy resin, the problem of easy corrosion and insufficient strength in acid and alkaline substances is solved. The corrosion resistance and high gloss of ceramic products are achieved.
Patent Information
- Application Number
- CN202411534204.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Traditional ceramic products are prone to corrosion when exposed to different acid and alkaline substances, have a short service life, and the smooth glaze ceramics are insufficient in strength and are prone to breaking.
Corrosion-resistant ceramic glaze composed of inner layer and outer layer material. The inner layer material is mainly composed of kaolin, quartz, zirconium carbonate and boron nitride, and the outer layer material is epoxy resin, diatomaceous earth and graphene. It is composed of other materials, and ceramic products are prepared through specific mixing ratios and process steps.
It improves the corrosion resistance and strength of ceramic products, extends the service life, and gives ceramic products high gloss.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to a ceramic glaze with corrosion resistance and a method for preparing ceramic products using the same. Background Art
[0002] With the development of society, consumers have different demands for ceramic products. Some pursue beautiful ceramic handicrafts, while others pursue practical daily ceramic products. Among them, daily ceramic products, such as tableware and kitchenware, sometimes come into contact with solids or liquids with different acidity and alkalinity. If they do not have acid and alkali corrosion resistance, the service life of ceramic products will not be long.
[0003] Traditional ceramic products are calcined after glazing. The smooth glazed ceramics obtained are also very easy to break if they are not strong enough. Therefore, the society urgently needs to develop a ceramic glaze with high strength, safety and corrosion resistance. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a ceramic glaze with high strength, safety and corrosion resistance.
[0005] The present invention adopts the following technical solution: A corrosion-resistant ceramic glaze, composed of an inner layer material and an outer layer material, wherein the inner layer material comprises the following components by weight: 60-72 parts of kaolin, 10-15 parts of quartz, 8-11 parts of zirconium carbonate, 10-12 parts of graphene, 7-10 parts of potassium feldspar, 7-10 parts of sodium feldspar, and 9-12 parts of boron nitride; The outer layer material comprises the following components in parts by mass: 75-80 parts of epoxy resin, 8-11 parts of diatomaceous earth, 11-15 parts of graphene, 12-15 parts of basalt powder, 10-13 parts of cashew nut shell oil, and 11-13 parts of diisopropanolamine.
[0006] The method for preparing a ceramic product using the ceramic glaze with corrosion resistance comprises the following steps: Step 1: Prepare the inner layer material: According to the mass fractions, kaolin, quartz, zirconium carbonate, potassium feldspar, sodium feldspar, and boron nitride are mixed and crushed to obtain a crushed material, and graphene and the crushed material are mixed and ball-milled to obtain an inner layer material; Step 2: Prepare the outer layer material According to the mass fraction, the epoxy resin is continuously stirred, and then cashew nut shell oil, diatomaceous earth, graphene, basalt powder and diisopropanolamine are added in sequence at intervals of 5 to 10 minutes to obtain an outer layer material; Step 3: Apply inner layer material and fire The inner layer material obtained in step 1 is mixed with water to a Baume degree of 46-50, and then coated on the ceramic body, dried and fired, and cooled to obtain a fired product; Step 4: Apply outer layer material and cure The outer layer material obtained in step 2 is coated on the surface of the fired product obtained in step 3, and solidified, and then cooled to obtain a corrosion-resistant ceramic product.
[0007] Furthermore, during the ball milling in step 1, the ball milling is performed at a mass ratio of ball: water: crushed material = 1:1.1~1.3:1, the rotation speed of the ball mill is 500~600r / min, and the ball milling time is 24~36h.
[0008] Furthermore, the drying temperature in step 3 is 70-80° C., and the drying time is 12-24 hours.
[0009] Further, the specific process of firing in step 3 is as follows: The temperature is raised to 1230-1250°C at a heating rate of 0.9-1.1°C / min, maintained at a constant temperature for 2-3 hours, and then cooled to obtain a sintered product.
[0010] Furthermore, the coating thickness in step 4 is 0.9-1.1 mm, and during the curing process, the temperature is raised to 100-110° C. at a heating rate of 0.6-0.8° C. / min and maintained at a constant temperature for 60-70 minutes.
[0011] Compared with the prior art, the present invention has the following beneficial effects: The corrosion-resistant ceramic glaze of the present invention is composed of an inner layer material and an outer layer material. The inner layer material is mainly composed of kaolin as the main material, quartz, zirconium carbonate and boron nitride are used in combination, and graphene is added to form a glaze inner layer after mixing, which ensures the molding of the ceramic and fixes the contour of the glaze. In addition, the outer layer material is mainly composed of epoxy resin as the main material, diisopropanolamine as the curing agent, diatomaceous earth, graphene, basalt powder and cashew nut shell oil are added, and a transparent outer glaze is formed after curing to meet the corrosion resistance requirements. DETAILED DESCRIPTION
[0012] The raw materials used in the present invention are all commercially available products. Example 1
[0013] A corrosion-resistant ceramic glaze, composed of an inner layer material and an outer layer material, wherein the inner layer material comprises the following components by weight: 60 parts of kaolin, 10 parts of quartz, 8 parts of zirconium carbonate, 10 parts of graphene, 7 parts of potassium feldspar, 7 parts of sodium feldspar, and 9 parts of boron nitride; The outer layer material includes the following components by weight: 75 parts of epoxy resin, 8 parts of diatomaceous earth, 11 parts of graphene, 12 parts of basalt powder, 10 parts of cashew nut shell oil, and 11 parts of diisopropanolamine.
[0014] The method for preparing a ceramic product using a ceramic glaze having corrosion resistance comprises the following steps: Step 1: Prepare the inner layer material: According to the mass fraction, kaolin, quartz, zirconium carbonate, potassium feldspar, sodium feldspar, and boron nitride are mixed and crushed to obtain a crushed material, and graphene and the crushed material are mixed and ball-milled. During the ball milling, the mass ratio of ball: water: crushed material = 1:1.1:1 is adopted for ball milling. The rotation speed of the ball mill is 500r / min, and the ball milling time is 24h, so as to obtain an inner layer material; Step 2: Prepare the outer layer material According to the mass fraction, the epoxy resin is continuously stirred, and then cashew nut shell oil, diatomaceous earth, graphene, basalt powder and diisopropanolamine are added in sequence at intervals of 5 minutes to obtain an outer layer material; Step 3: Apply inner layer material and fire The inner layer material obtained in step 1 is mixed with water to a Baume degree of 46, and then coated on the ceramic body for drying at a temperature of 70°C for 12 hours, and then fired at a heating rate of 0.9°C / min to 1230°C, kept at a constant temperature for 2 hours, and cooled to obtain a fired product; Step 4: Apply outer layer material and cure The outer layer material obtained in step 2 is coated on the surface of the fired product obtained in step 3, with a coating thickness of 0.9 mm. Then, a curing treatment is performed, and the temperature is increased to 100°C at a heating rate of 0.6°C / min, and the temperature is kept constant for 60 minutes. After cooling, a corrosion-resistant ceramic product is obtained. Example 2
[0015] A ceramic glaze with corrosion resistance, composed of an inner layer material and an outer layer material, wherein the inner layer material comprises the following components by weight: 72 parts of kaolin, 15 parts of quartz, 11 parts of zirconium carbonate, 12 parts of graphene, 10 parts of potassium feldspar, 10 parts of sodium feldspar, and 12 parts of boron nitride; The outer layer material includes the following components by mass: 80 parts of epoxy resin, 11 parts of diatomaceous earth, 15 parts of graphene, 15 parts of basalt powder, 13 parts of cashew nut shell oil, and 13 parts of diisopropanolamine.
[0016] The method for preparing a ceramic product using a ceramic glaze having corrosion resistance comprises the following steps: Step 1: Prepare the inner layer material: According to the mass fraction, kaolin, quartz, zirconium carbonate, potassium feldspar, sodium feldspar, and boron nitride are mixed and crushed to obtain a crushed material, and graphene and the crushed material are mixed and ball-milled. During the ball milling, the mass ratio of ball: water: crushed material = 1:1.3:1 is adopted for ball milling. The rotation speed of the ball mill is 5600r / min, and the ball milling time is 36h, so as to obtain an inner layer material; Step 2: Prepare the outer layer material According to the mass fraction, the epoxy resin is continuously stirred, and then cashew nut shell oil, diatomaceous earth, graphene, basalt powder and diisopropanolamine are added in sequence at intervals of 10 minutes to obtain an outer layer material; Step 3: Apply inner layer material and fire The inner layer material obtained in step 1 is mixed with water to a Baume degree of 50, and then coated on the ceramic body for drying at a temperature of 80°C for 24 hours, and then fired at a heating rate of 1.1°C / min to 1250°C, kept at a constant temperature for 3 hours, and cooled to obtain a fired product; Step 4: Apply outer layer material and cure The outer layer material obtained in step 2 is coated on the surface of the fired product obtained in step 3, with a coating thickness of 1.1 mm. Then, a curing treatment is performed, and the temperature is increased to 110°C at a heating rate of 0.8°C / min, and the temperature is kept constant for 70 minutes. After cooling, a corrosion-resistant ceramic product is obtained. Example 3
[0017] A corrosion-resistant ceramic glaze, composed of an inner layer material and an outer layer material, wherein the inner layer material comprises the following components by weight: 68 parts of kaolin, 13 parts of quartz, 10 parts of zirconium carbonate, 11 parts of graphene, 9 parts of potassium feldspar, 8 parts of sodium feldspar, and 10 parts of boron nitride; The outer layer material includes the following components by mass: 78 parts of epoxy resin, 10 parts of diatomaceous earth, 13 parts of graphene, 14 parts of basalt powder, 11 parts of cashew nut shell oil, and 12 parts of diisopropanolamine.
[0018] The method for preparing a ceramic product using a ceramic glaze having corrosion resistance comprises the following steps: Step 1: Prepare the inner layer material: According to the mass fractions, kaolin, quartz, zirconium carbonate, potassium feldspar, sodium feldspar, and boron nitride are mixed and crushed to obtain a crushed material, and graphene and the crushed material are mixed and ball-milled. During the ball milling, the ball milling is performed at a mass ratio of ball: water: crushed material = 1:1.2:1, the rotation speed of the ball mill is 550r / min, and the ball milling time is 30h, so as to obtain an inner layer material; Step 2: Prepare the outer layer material According to the mass fraction, the epoxy resin is continuously stirred, and then cashew nut shell oil, diatomaceous earth, graphene, basalt powder and diisopropanolamine are added in sequence at intervals of 8 minutes to obtain an outer layer material; Step 3: Apply inner layer material and fire The inner layer material obtained in step 1 is mixed with water to a Baume degree of 48, and then coated on the ceramic body for drying at a temperature of 75°C for 20 hours, and then fired at a heating rate of 1.0°C / min to 1240°C, kept at a constant temperature for 2.5 hours, and cooled to obtain a fired product; Step 4: Apply outer layer material and cure The outer layer material obtained in step 2 is coated on the surface of the fired product obtained in step 3 with a coating thickness of 1.0 mm. Then, a curing treatment is performed, and the temperature is increased to 105°C at a heating rate of 0.7°C / min and kept at a constant temperature for 65 minutes. After cooling, a corrosion-resistant ceramic product is obtained.
[0019] Comparison example
[0020] A corrosion-resistant ceramic glaze, composed of an inner layer material and an outer layer material, wherein the inner layer material comprises the following components by weight: 68 parts of kaolin, 13 parts of quartz, 10 parts of zirconium carbonate, 11 parts of graphene, 9 parts of potassium feldspar, 8 parts of sodium feldspar, and 10 parts of boron nitride; The outer layer material includes the following components by weight: 78 parts of epoxy resin, 10 parts of diatomaceous earth, and 12 parts of diisopropanolamine.
[0021] The method for preparing a ceramic product using a ceramic glaze having corrosion resistance comprises the following steps: Step 1: Prepare the inner layer material: According to the mass fractions, kaolin, quartz, zirconium carbonate, potassium feldspar, sodium feldspar, and boron nitride are mixed and crushed to obtain a crushed material, and graphene and the crushed material are mixed and ball-milled. During the ball milling, the ball milling is performed at a mass ratio of ball: water: crushed material = 1:1.2:1, the rotation speed of the ball mill is 550r / min, and the ball milling time is 30h, so as to obtain an inner layer material; Step 2: Prepare the outer layer material According to the mass fraction, the epoxy resin is continuously stirred, and then diatomaceous earth and diisopropanolamine are added in sequence at intervals of 8 minutes to obtain an outer layer material; Step 3: Apply inner layer material and fire The inner layer material obtained in step 1 is mixed with water to a Baume degree of 48, and then coated on the ceramic body for drying at a temperature of 75°C for 20 hours, and then fired at a heating rate of 1.0°C / min to 1240°C, kept at a constant temperature for 2.5 hours, and cooled to obtain a fired product; Step 4: Apply outer layer material and cure The outer layer material obtained in step 2 is coated on the surface of the fired product obtained in step 3 with a coating thickness of 1.0 mm. Then, a curing treatment is performed, and the temperature is increased to 105°C at a heating rate of 0.7°C / min and kept at a constant temperature for 65 minutes. After cooling, a corrosion-resistant ceramic product is obtained.
[0022] The corrosion-resistant ceramic products prepared in Examples 1 to 3 of the present invention and the corrosion-resistant ceramic products prepared in the comparative example were tested, wherein: Use GB / T 34252-2017 Test method for glaze crack resistance of daily-use ceramics to test crack resistance; Use GB / T 3532-2022 Daily-use porcelain to test glossiness; The test results are shown in Table 1 below: Table 1: Test results
[0023] It can be seen from Table 1 that the corrosion-resistant ceramic products prepared in Examples 1 to 3 have excellent corrosion resistance and high gloss.
[0024] The above is a preferred embodiment of the present invention, and it should be noted that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered as the protection scope of the present invention.
Claims
1. A ceramic glaze with corrosion resistance, characterized in that: It is composed of an inner layer material and an outer layer material, wherein the inner layer material includes the following components by weight: 60-72 parts of kaolin, 10-15 parts of quartz, 8-11 parts of zirconium carbonate, 10-12 parts of graphene, 7-10 parts of potassium feldspar, 7-10 parts of sodium feldspar, and 9-12 parts of boron nitride; The outer layer material comprises the following components in parts by mass: 75-80 parts of epoxy resin, 8-11 parts of diatomaceous earth, 11-15 parts of graphene, 12-15 parts of basalt powder, 10-13 parts of cashew nut shell oil, and 11-13 parts of diisopropanolamine.
2. A method for preparing a ceramic product using the corrosion-resistant ceramic glaze according to claim 1, characterized in that: The steps include: Step 1: Prepare the inner layer material: According to the mass fractions, kaolin, quartz, zirconium carbonate, potassium feldspar, sodium feldspar, and boron nitride are mixed and crushed to obtain a crushed material, and graphene and the crushed material are mixed and ball-milled to obtain an inner layer material; Step 2: Prepare the outer layer material According to the mass fraction, the epoxy resin is continuously stirred, and then cashew nut shell oil, diatomaceous earth, graphene, basalt powder and diisopropanolamine are added in sequence at intervals of 5 to 10 minutes to obtain an outer layer material; Step 3: Apply inner layer material and fire The inner layer material obtained in step 1 is mixed with water to a Baume degree of 46-50, and then coated on the ceramic body, dried and fired, and cooled to obtain a fired product; Step 4: Apply outer layer material and cure The outer layer material obtained in step 2 is coated on the surface of the fired product obtained in step 3, and solidified, and then cooled to obtain a corrosion-resistant ceramic product.
3. The method for preparing a ceramic product according to claim 2, characterized in that: During the ball milling in step 1, the mass ratio of ball: water: crushed material = 1: 1.1 ~ 1.3: 1 is adopted for ball milling, the rotation speed of the ball mill is 500 ~ 600r / min, and the time of the ball milling is 24 ~ 36h.
4. The method for preparing a ceramic product according to claim 2, characterized in that: The drying temperature in step 3 is 70-80°C, and the drying time is 12-24 hours.
5. The method for preparing a ceramic product according to claim 2, characterized in that: The specific process of firing described in step 3 is as follows: Increase the temperature to 1230~1250℃ at a heating rate of 0.9~1.1℃ / min and keep the temperature constant for 2~3h.
6. The method for preparing a ceramic product according to claim 2, characterized in that: The coating thickness in step 4 is 0.9-1.1 mm. During the curing process, the temperature is raised to 100-110° C. at a heating rate of 0.6-0.8° C. / min and the temperature is kept constant for 60-70 minutes.
Citation Information
Patent Citations
Epoxy resin composition used for shielding deep well submersible pump and casting method thereof
CN101671426A
Ceramic plate for cooking bench, and preparation and application method thereof
CN104193296A
Novel salt mist-resistant epoxy anticorrosive paint
CN106118377A
Process for preparing graphene daily ceramic material
CN107304129A
Graphene oxide hybrid alumina corrosion-resistant ceramic coating and preparation method thereof
CN109761584A